2018
DOI: 10.1248/bpb.b17-00749
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Pharmacist Interventions on Pain Control and Side Effect Management in Outpatients with Cancer Receiving Opioid Treatments

Abstract: For improving the QOL of patients diagnosed with cancer, early palliative care is recommended, aiming to minimize pain and opioid-induced side effects. Herein, we evaluated the effect of continuous interventions for pain management and opioid-induced side effects in outpatients with cancer. Pharmacists continuously performed interventions on patients on their hospital visits, starting from the first visit for opioid introduction to intervention via telephone. We recorded their pain patterns and intensities, us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 21 publications
0
35
0
2
Order By: Relevance
“…Cancer diagnosis may lead to demoralization of NSCLC patients, such as hopelessness and helplessness, which can lead to suicidal ideation 39. Poor consequences of cancer treatment may bring physical and mental pain to NSCLC patients 40. It has been reported that cancer patients with low socioeconomic status and family support are more likely to suicide 41.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer diagnosis may lead to demoralization of NSCLC patients, such as hopelessness and helplessness, which can lead to suicidal ideation 39. Poor consequences of cancer treatment may bring physical and mental pain to NSCLC patients 40. It has been reported that cancer patients with low socioeconomic status and family support are more likely to suicide 41.…”
Section: Discussionmentioning
confidence: 99%
“…Some points are important to elucidate the difficulties in prescribing opioids when treating cancer pain, such as inadequate pain assessment, as only a small number of physicians reported applying pain management guidelines in their practice; 23 to 31% of physicians tend to delay the adoption of strong opioids until patients reach the terminal stage of their disease, or until their pain becomes intractable due to the difficulty in managing adverse effects; 25 to 40% of physicians are concerned about opioid addiction, and there is even greater fear in patients with a family history of addiction. Moreover, although oncologists have shown excellent basic knowledge about the use of opioids to treat cancer pain than physicians in other specialties, there is still a significant information deficit within their specialty 15,24,27,37,39,41 . From the patient's perspective, other potential barriers to the use of opioids may include lack of communication with physicians, resulting in insufficient notification of symptoms; misconceptions about the pain drug due to the fear of adverse effects, dependence, tolerance, and reduced immunity; and fatalistic beliefs, i.e., if the pain is increasing, the idea of inevitable and uncontrollable progression of the disease is created.…”
Section: Final Considerationsmentioning
confidence: 99%
“…10) While NRS is helpful for assessing current pain intensity, it is reported that multiple measures evaluating the complex causes and consequences of pain are needed. 11) We previously reported that pain evaluation using the NRS during opioid treatment in combination with repeated pharmacist interviews and telephone counseling improved pain relief among outpatients with cancer. 12) However, our previous study did not focus on the relationship between pain and QOL.…”
Section: Introductionmentioning
confidence: 99%